The Forms and Functions of Constructed Languages in 20th Century Dystopian Literature - Norha, Sasu (My University, 2023)
This thesis examines the use of constructed languages in 20th century dystopian literature. The aim of this thesis is to find what common functions constructed languages serve in dystopian literature, and what the constructed languages are like in terms of their linguistic forms. To accomplish this goal, I analyse three different constructed languages: Newspeak from George Orwell’s Nineteen Eighty-Four (1949), Nadsat from Anthony Burgess’ A Clockwork Orange (1962) and Láadan from Suzette Haden Elgin’s Native Tongue trilogy (1984, 1987, 1994). I examine the languages individually in terms of their forms and functions, after which I move on to compare them with each other to find their differences and similarities in function both from the perspective of their historical context as well as the modern day. I found that while the languages are very different in terms of their linguistic forms, they all share certain functions. Most prominently, they tend to comment on themes of linguistic relativity, and they are used to build both individual and group identities among other functions. In future research these findings on constructed languages in dystopian literature could be examined in contrast to other genres of literature.
Keywords: Dystopian Literature, Constructed Languages, Native Tongue, Nineteen Eighty-Four, A Clockwork Orange